Design the Roadmap of Holistic Financial Inclusion for Baitul Maal wat Tamwil - . Ascarya; Siti Rahmawati; Hendri Tanjung (Institute for Research and Community Empowerment (LPPM TAZKIA), 2018)
This paper aims to design the roadmap of Holistic Financial Inclusion (HFI) by Baitul Maal wat Tamwil (BMT), where Baitul Maal carries out social inclusion and Baitut Tamwil carries out financial inclusion, using Analysis Network Process (ANP). The results show that the most important aspects of HFI are Sustainability, Development Program, Financing Program and Islamic Microfinance Services, while the most important elements of HFI are regular meeting, micro savings, simplicity and easy access, consumption smoothing, bailout debt, savings program and income increase, followed by funding independent, total deposits, mindset change, and micro financing. HFI of BMT could be developed gradually. At the first stage, BMT should have the minimum 16 elements of HFI comprising 4 (four) Social Inclusion elements, 4 (four) Financial Inclusion elements, 4 (four) Double bottom-Line elements and 4 (four) Welfare Impact elements. At the second stage, BMT should add the next 16 elements comprising 5 (five) Social Inclusion elements and 3 (three) Financial Inclusion elements, 5 (five) Double Bottom-Line elements and 3 (three) Welfare Impact elements. Moreover, at the third stage, the remaining 24 elements of HFI should be fulfilled. All Islamic financial institution must have the characteristic of HFI.